Assessment of the impact of military operations on agricultural land use - Olishevskyi, V. (Land Management, Cadastre and Land Monitoring, 2024)
The analysis made in terms of this research shows, that the military-technogenic load leads to high levels of pollution of the territory with oil products, lead, cadmium and aromatic hydrocarbons. The impact of military operations on agricultural land use in the territory of the Bucha city territorial community of Bucha district of Kyiv oblast is assessed. The level of damage to agricultural land affected by military actions is investigated. To calculate the assessment of the impact of military actions on agricultural land use, the "Visual Determination of Land Damage Levels" was used. The amount of damage caused by hostilities to agricultural land use was calculated. The method of expert assessment was used to calculate the economic level of damage caused by hostilities. The ecological condition of the soil within the Bucha urban community was determined. To assess the ecological condition of the soil, an indicator of the ecological stability of the territory in the post-war period was calculated and compared to the pre-war period. Taking into account the proposed research methods and their results, it is analysed that agricultural land within the territory of the Bucha city territorial community can be used for any crops, but the harvested products’ quality have to be controlled. There is a need for agrotechnical measures to reduce the impact of metals on agricultural products.